2022
DOI: 10.1101/2022.04.21.489001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative assessment of the transcriptome and virome of the poultry red mite Dermanyssus gallinae

Abstract: Dermanyssus gallinae is a blood-feeding mite that parasitises on wild birds and farmed poultry. The D. gallinae mite has a short life cycle of fewer than two weeks from the egg to an egg-laying female. The remarkably swift processing of blood, together with the capacity to blood-feed in most developmental stages, makes this mite a highly debilitating pest. We have constructed developmental stage-specific transcriptomes, through Illumina RNA-seq, to mine the repertoire of protein-encoding mRNA transcripts, prod… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 109 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…The transcriptome analysis of PRM sequences revealed that reads of CP genes accounted for ~62% of all protease-encoding reads. Among these, 80% were cathepsin L-like proteases of the midgut [ 32 ]. In addition, expression of PRM-CP ( Deg-CPR-1 ) has previously been observed in the midgut using laser capture microdissection and RT-PCR [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome analysis of PRM sequences revealed that reads of CP genes accounted for ~62% of all protease-encoding reads. Among these, 80% were cathepsin L-like proteases of the midgut [ 32 ]. In addition, expression of PRM-CP ( Deg-CPR-1 ) has previously been observed in the midgut using laser capture microdissection and RT-PCR [ 18 ].…”
Section: Discussionmentioning
confidence: 99%